Analysis of Factors Affecting The Welfare of Non-Working Elderly in Denpasar City - Made Ayu Gita Nindya Sari; Anak Agung Ketut Ayuningsasi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Elderly people who do not work have the right to receive welfare just like the rest of the population, so an understanding of the factors that influence the welfare of the elderly is needed. This research aims (1) to analyze the influence of health, old age benefits and social support simultaneously on the welfare of unemployed elderly in Denpasar City; (2) to analyze the partial influence of health, old age benefits and social support on the welfare of the elderlydoes not work in Denpasar City. The research on elderly people in Denpasar City took samples from four sub-districts, namely West Denpasar, East Denpasar, South Denpasar and North Denpasar. The elderly population was 72,680 people and the sample size was 100 people. Sampling was carried out using purposive sampling and data analysis using confirmatory factor analysis and multiple linear regression analysis. Based on the research results, information was obtained that health, old age benefits and social support have a significant simultaneous and partial influence on the welfare of elderly people who do not work in Denpasar City. This means that as the health, old age benefits and social support of the elderly who do not work improve, the welfare of the elderly who do not work in Denpasar City will increase.